2017
DOI: 10.1158/1078-0432.ccr-16-2366
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of Programmed Cell Death-1 and Its Ligand Expression as Discriminatory and Predictive Markers in Ovarian Cancer

Abstract: Purpose: We aimed to establish whether programmed cell death-1 (PD-1) and programmed cell death ligand 1 (PD-L1) expression, in ovarian cancer tumor tissue and blood, could be used as biomarkers for discrimination of tumor histology and prognosis of ovarian cancer. Experimental Design: Immune cells were separated from blood, ascites, and tumor tissue obtained from women with suspected ovarian cancer and studied for the differential expression of possible immune biomarkers using flow cytometry. P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 25 publications
5
50
0
Order By: Relevance
“…In ovarian cancer, it has been shown that total PD-L1 and CD14þ/PD-L1þ expression in the peripheral blood can accurately differentiate between benign tumours and Stage I malignant ovarian tumours as well as showing significant differential expression between early and late-stage disease [68].…”
Section: Blood Basedmentioning
confidence: 99%
“…In ovarian cancer, it has been shown that total PD-L1 and CD14þ/PD-L1þ expression in the peripheral blood can accurately differentiate between benign tumours and Stage I malignant ovarian tumours as well as showing significant differential expression between early and late-stage disease [68].…”
Section: Blood Basedmentioning
confidence: 99%
“…These observations suggest that PD-L1 expression may reflect aggressive biological potential and play an important role in tumour immune escape. For example, in ovarian cancer, the differential expression of immunological markers related to the PD-1/PD-L1 pathway in blood can be used as potential diagnostic and prognostic markers [13]. PD-L1 is also expressed by macrophages in ovarian cancer and is strongly associated with both effector and regulatory tumour infiltrating lymphocyte (TIL) subsets [14].…”
Section: Introductionmentioning
confidence: 99%
“…TICS is built on the principles of an allogeneic response but has been specifically optimised to quantify activation of multiple human lymphocyte subsets and subsequent cancer cell killing upon PD-1/L1 blockade. Although we have previously reported the differential expression pattern and prognostic value of PD-L1 on human myeloid cells isolated from ovarian cancer patients [16], removal of monocytes from TICS is necessary to demonstrate the effects of immune checkpoint blocking antibody and to reduce donor-to-donor variability.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%